Dichlorine peroxide (ClOOCl), chloryl chloride (ClCl(O)O) and chlorine chlorite (ClOClO): very accurate ab initio structures and actinic degradation. Issue 7 (7th February 2020) - Ferchichi, Olfa; Derbel, Najoua; Cours, Thibaud; Alijah, Alexander
Abstract : The structural parameters of the three most stable isomers with formula Cl2 O2, dichlorine peroxide, chloryl chloride and chlorine chlorite, were determined by high-level ab initio theory. The photodissociation pathways were investigated. Abstract : The structural parameters of the three most stable isomers with formula Cl2 O2, dichlorine peroxide, chloryl chloride and chlorine chlorite, were determined by high-level ab initio theory. The effects of core–valence electronic correlation as well as relativistic corrections were included in the calculations, and vibrational averaging of the so-obtained structures was performed. The bond distances agree with experimental data, where available, to within 0.01 Å, an unprecedented accuracy in particular for the floppy dichlorine peroxide molecule. The UV spectra of the three molecules were computed and decay pathways investigated. Under actinic UV radiation at 248 nm dichlorine peroxide decomposes principally according to ClOOCl → 2Cl + O2, in a synchronous concerted mechanism. In the low-energy tail region of this signal, the decay proceeds in a non-synchronous manner. There is also a low probability of the decay channel towards ClOO + Cl, whereas ClO molecules were not found. Chloryl chloride absorbs strongly around 300 nm. It disintegrates into ClO2 + Cl, where ClO2 seems to be formed mainly in excited electronic states which decompose further into Cl + O2 . Hence chloryl chloride, though much less abundant in the stratosphere than dichlorine peroxide, also contributes to ozone depletion.